The hallmarks of aging as a conceptual framework for health and longevity research - Tartiere, Antonio G.; Freije, José M. P.; López-Otín, Carlos (Frontiers in Aging, 2024)
The inexorability of the aging process has sparked the curiosity of human beings since ancient times. However, despite this interest and the extraordinary scientific advances in the field, the complexity of the process has hampered its comprehension. In this context, The Hallmarks of Aging were defined in 2013 with the aim of establishing an organized, systematic and integrative view of this topic, which would serve as a conceptual framework for aging research. Ten years later and promoted by the progress in the area, an updated version included three new hallmarks while maintaining the original scope. The aim of this review is to determine to what extent The Hallmarks of Aging achieved the purpose that gave rise to them. For this aim, we have reviewed the literature citing any of the two versions of The Hallmarks of Aging and conclude that they have served as a conceptual framework not only for aging research but also for related areas of knowledge. Finally, this review discusses the new candidates to become part of the Hallmarks list, analyzing the evidence that support whether they should or should not be incorporated.